Ethical Aspects of Using Animals in Experimental Procedures - Gądzik, Zuzanna (Studia Ecologiae et Bioethicae, 2021)
This article deals with an analysis of the ethical aspects of using animals in experimental procedures - in the context of causing animals, pain or suffering. It covers the compilation and characterisation of the views of supporters and opponents of conducting experiments on animals. On the one hand, the findings of the above procedures may be important for the development of science (including medical and veterinary sciences), technology or industry, whilst on the other hand, they are often associated with pain or the suffering of living organisms, and have a negative impact on their health, or even life. This topic is the subject of scientific and ethical discussion, and attempts to find a compromise, that would allow the acquisition of reliable test results, and eliminate, or at least, reduce the negative consequences for animals used in them. The article refers to issues of altruistic and egoistic positions, species chauvinism, and the so-called 3R principles (replacing, reducing, refining). The article is primarily due to the entry into force of the Act of the 15th of January, 2015, on the protection of animals used for scientific or educational purposes, repealing the existing Act of the 21st of January, 2005, on animal experiments, and re-regulating issues related to the viability of using live animals in experimental procedures, exposing them to pain or suffering.